Technological mediation: new scenarios for teaching practice (2016)
The objective of this article is to elucidate and reflect on the dimensions configured in a transformation of teaching practices. Such practices can lead to set new educational scenarios based on technological mediation. This paper is the result of a qualitative analysis of concepts referred to in researches between 2009 and 2013. Likewise it makes part of the project: ‘Theoretical Approaches of Research Projects on Mediation of Information and Communication Technologies: A Configuration for a Conceptual Approach’, product of the announcement # 9 by Universidad Santo Tomas’ Distance Learning – Open University Vice Chancellor Office (VUAD). It is inquired, among other emerging categories, about autonomous and collaborative learning, the role of online tutors, the social, teaching, and cognitive presence, the collective intelligence and the digital education. Methodologically dissertation was based on the use of ATLAS.ti – program that strengthened the process of ordering and organizing the information from various sources, and helped to determine the categorization and construction of semantic maps. Finally, conclusions and questions about prospects for technology and education are presente.